HUBUNGAN UMUR, KEBISINGAN DAN TEMPERATUR UDARA DENGAN KELELAHAN SUBJEKTIF INDIVIDU DI PT X JAKARTA - Karina Wahyu Andriani (The Indonesian Journal of Occupational Safety and Health, 2016)
Fatigue is one of the causes of accidents. According Setyawati (2010) fatigue shown to contribute more than 60% in the event of an accident. This reseacrh was conducted to determine the relationship of the individual characteristics, noise and air temperature with subjective fatigue. Fatigue can be caused by various factors of education, health, habits, motivation, temperature, radiation, and humidity to the air and noise work environment. reseacrh observational descriptive with cross sectional approach. The number of samples this study were 45 people, were taken by simple random sampling. The independent variables were age, noise and air temperature. The dependent variable of this study was fatigue. The statistical test used chi-square test. Primary data were obtained from interviews and measurements directly. Measurements were taken at two locations new office and workshop 9. The results of this study showed that 45 respondents (88.90%) had mild fatigue, and 5 respondents (11.10%) experienced moderate fatigue. All respondents who experienced fatigue being exposed to noise and temperature exceeding the standarize. The conclusion from this study is there is no significant relationship between noise (p = 0.31) and air temperature (p = 0.41) with subjective fatigue. While age with subjective fatigue have a significant relationship with the value (p = 0.61). Advice for company made policy so workers over 40 years old can be get jobs that match their abilities.Keywords: age, noise, temperature, fatigue